2007
DOI: 10.2466/pr0.100.2.509-519
|View full text |Cite
|
Sign up to set email alerts
|

Deductive Reasoning and Creativity: A Cross-Cultural Study

Abstract: The present cross-cultural study examined the relationship between deductive reasoning and creativity among college students (M age=20.4 yr., SD= .6) from Hong Kong (n=39) and the United States (n=38). Participants performed tasks designed to measure deductive reasoning, creative writing, and insight problem-solving, all in verbal form. No correlation was found between the performance for deductive reasoning and creativity as measured by creative writing. Insight problem-solving performance correlated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Niu et al. () found in their cross‐cultural study that Chinese and Americans displayed no differences in verbal deductive reasoning.…”
Section: Influences Of Culture On Cognitive Abilitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Niu et al. () found in their cross‐cultural study that Chinese and Americans displayed no differences in verbal deductive reasoning.…”
Section: Influences Of Culture On Cognitive Abilitiesmentioning
confidence: 96%
“…Gardner () contended this emphasis in acquiring knowledge and skills in such environments discourages creativity development. Indeed, numerous studies (Niu, Zhang & Yang, ; Niu & Sternberg, , ) found Americans to be more creative than Chinese counterparts.…”
Section: Influences Of Culture On Cognitive Abilitiesmentioning
confidence: 99%
“…In deductive reasoning, concepts do not need to be synthesized or rearranged. Interestingly, Niu, Zhang and Yang (2007), found no correlation between deductive thinking and creativity. In contrast, Vartanian, Martindale, and Kwiatkowski (2003) show a correlation between creativity and inductive thinking.…”
Section: Scientific Creativity and Social Factorsmentioning
confidence: 99%
“…Though it takes different forms in the creativity realm and does not explain the process, reasoning, plays a role in creativity development (Runco, ). Fasko () points out that studies explicitly connecting the concepts of reasoning and creativity are scarce, but some do exist in the literature (e.g., Niu, Zhang & Yang, ). A clear link exists between creativity and learning (Beghetto & Plucker, ).…”
Section: Metacognition and Creativitymentioning
confidence: 99%